Social and Climate Change: Impact on Human Behavior - Koentjoro Soeparno; Budi Andayani (ANIMA Indonesian Psychological Journal, 2014)
The nature of social change occurs at the center of human consciousness and based on a commitment, it cannot be reversed, rejected, or canceled (Vago, 2004). Therefore, there are economic and political orders as a result of conflict of ideologies within society. Historically, global social change is caused by the Industrial Revolution and Ideology and Gender Revolution. The invention of telegraph was the beginning of globalization, identified by the 4T revolution (Telecommunications, Transport, Tourism and Transparency). The revolution in agriculture, mining, manufacturing and industry results changes in lifestyle and exploitation of natural resources that can cause climate change. The second source of social change is the revolution of ideology and gender. When colonialism, slavery and deprivation of human rights occurred, the movement to struggle for human rights as its counterculture appeared, resulting in 1980 the pro-human right movement products. The sexual revolution in the 1960s in the USA demanded for equal rights between men and women. The 1975 UNFPA population convention held in Cairo have made an agreement to restrict population growth using contraception, resulting later-on the concept that sex is no longer for reproductive purpose but for recreation. People’s lifestyle has changed since then.